Onobrychis mehmetchiquii (Fabaceae) sp. nov, a new species from European Turkey - Aybeke, Mehmet; Dane, Feruzan (Phytotaxa, 2017)
A new Onobrychis taxon was collected from regions of Turkey that reside in Europe and is described as Onobrychis mehmetchiquii Aybeke & Dane sp. nova belonging to sect. Onobrychis. Additionally, a description of the species along with illustrations and key features are given in contrast to O. alba and O. degenii which are the most similar to the new taxon.